Effect of antioxidant supplementation on urine and blood markers of oxidative stress during extended moderate-altitude training - Pfeiffer, J. M.; Askew, E. W.; Roberts, D. E.; Wood, S. M.; Benson, J. E.; Johnson, S. C.; Freedman, M. S. (Wilderness and Environmental Medicine, 1999)
OBJECTIVE: To investigate the increase in oxidative stress during work at moderate altitudes due to additional energy expenditure, tissue anoxia, and UV light exposure. METHODS: Thirty US Marine Corps volunteers were divided into placebo (P) and antioxidant supplement (S) groups and tested for markers of oxidative stress before (t0), at the midpoint of (t1), and after (t2) 14 days of winter training at a moderate altitude (approximately 2700 m). The antioxidant supplement consisted of a daily dose of 20,000 IU beta-carotene, 400 IU vitamin E, 500 mg vitamin C, 100 micrograms selenium, and 30 mg zinc. The following markers of oxidative stress were measured: urine thiobarbituric acid reactive substances (TBARSs), urine hydroxynonenal (HNE), urine 8-hydrodeoxyguanosine (8-OHdG), plasma total peroxyl radical trapping potential (TRAP), and plasma lipid hydroperoxides (LPOs). Urine was collected on a 24-hr basis at t0, t1, and t2; blood samples were collected at t0 and t2. RESULTS: P group LPOs increased 30% (p < 0.05) between t0 and t2, whereas S group LPOs did not increase. Both groups exhibited significant increases in urine TBARSs, HNE, and 8-OHdG by t2. Urine TBARSs, HNE, and 8-OHdG increased between t0 and t1 in both groups, with the greater increase in the S group. The conflicting results between the plasma and urine markers of oxidative stress may be due to a time-phase relationship. CONCLUSIONS: The results of this study suggest that work in a moderate-altitude cold-weather environment is accompanied by increased oxidative stress, despite relatively high intakes of dietary and supplemental antioxidants.